Multimedia and interactivity in educational materials - Mališů, Petri; Šaloun, Petr (Technium Social Sciences Journal, 2020)
Teachers can choose from a group of different kinds of educational materials. These educational materials vary with their features, properties, and possibilities of use. Nowadays, teachers are using more digital educational materials, which are simple to use and offers advantages that come from their digital form. But not all digital materials provide significant benefits for effective education. The main features that improve the learning of students are multimedia and interactive elements. This paper contains a summary of multimedia and interactivity and different points of view on these terms.